The Impact of Personal Characteristics on Personal Branding in Reflection to the Employability - Pathmanathan, Prassanna; Dodamgoda, Nadeeja (Information Management and Business Review, 2018)
Unemployment is a major problem Sri Lanka is facing over the years. Although 22,000 graduates pass out every year from state and private universities, there is always a gap between what employers expect in a graduate and what the graduate could offer to the employer. This research focus on the employability of the IT graduates passing out from state and private universities, with specific reference to their personal characteristics and personal branding. Personal branding is a major concern with respect to the recruitment of any graduate. IT graduates especially are expected to have certain personal characteristics which determine their personal branding and influence their employability. The main objective of this research is to determine the impact of the personal characteristics such as personal identity, personal image and personal positioning on employability of IT graduates and to analyze their mediation effect with the personal branding. Further, an attempt is made to determine whether the personal branding and employability of IT graduates significantly differ based on the university type (state and private). The research mainly focuses on quantitative analysis by piloting a questionnaire to 300 IT graduates following a hypothetical deductive method. The findings through the quantitative data are followed up based on qualitative data collected through semi-structured interviews with HR and Recruitment Managers of IT companies. Findings of this research revealed that personal characteristics have a strong impact on the employability of an IT graduate and this relationship is mediated by personal branding. Further, IT graduates passing out from private sector universities have stronger personal characteristics and personal branding compared to the graduates passing out from state sector universities. Thus, they are more employable compared to IT graduates passing out from state sector universities in Sri Lanka.